Inhibition of neural stem cell aging through the transient induction of reprogramming factors. Issue 3 (28th June 2020) - Han, Min Ji; Lee, Won Ji; Choi, Joonhyuk; Hong, Yean Ju; Uhm, Sang Jun; Choi, Youngsok; Do, Jeong Tae
Abstract: Adult stem cells age during long‐term in vitro culture, and neural stem cells (NSCs), which can self‐renew and differentiate into neurons and glial cells, also display reduced differentiation potential after repeated passaging. However, the mechanistic details underlying this process remain unclear. In this study, we found that long‐term in vitro culture of NSCs resulted in aging‐related upregulation of inflammatory‐ and endoplasmic reticulum (ER) stress‐related genes, including the proinflammatory cytokines interleukin (IL)1β and IL6, the senescence‐associated enzyme matrix metallopeptidase 13 (MMP13), and the ER stress‐responsive transcription factor activating transcription factor 4 (ATF4) and C/EBP homologous protein (CHOP). However, the cyclic and transient induction of four reprogramming factors (POU domain, class 5, transcription factor 1, also known as octamer‐binding transcription factor 4; SRY [sex determining region Y]‐box 2; Kruppel‐like factor 4; and myelocytomatosis oncogene; collectively referred to as OSKM) can inhibit NSC aging, as indicated by the decreased expression of the inflammatory and ER stress‐related genes. We used ROSA‐4F NSCs, which express OSKM from only one allele, to minimize the potential for full reprogramming or tumor formation during NSC rejuvenation. We expect that this novel rejuvenation method will enhance the potential of NSCs as a clinical approach to the treatment of neurological diseases. Abstract : Long‐term in vitro culture of neural stem cells (NSCs) resulted in aging‐related upregulation of inflammatory‐ and endoplasmic reticulum (ER) stress‐related genes. The induction of four reprogramming factors (Oct4, Sox2, Klf4, and c‐Myc) could decrease expression of the inflammatory and ER stress‐related genes during the long‐term culture.